1992
DOI: 10.1016/0016-7037(92)90066-r
|View full text |Cite
|
Sign up to set email alerts
|

Refractory inclusions with unusual chemical compositions from the Vigarano carbonaceous chondrite

Abstract: Abstract-Ten inclusions, nine from Vigarano and one from Leoville, both members of the reduced subgroup of C3V chondrites, were analyzed for major and trace elements by neutron activation. Most have some refractory element characteristics that are common in refractory inclusions from Allende, a member of the oxidized subgroup of C3V chondrites. For instance, three (Leo 3537-2, Vig 1623-8, Vig 1623-11) are Type B inclusions with Group I or modified Group I REE patterns, three (Vig 1623-5, Vig 1623-10, Vig 1623-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Kimura and Ikeda (1996) found that many chondrules in Vigarano show alteration features similar to those in Allende: nepheline, sodalite, hedenbergite, fayalitic olivine rims around forsterite grains and fayalitic olivines replacing low-Ca pyroxene phenocrysts. Some CAIs in Vigarano experienced iron-alkali metasomatic alteration of melilite (Sylvester et al, 1992(Sylvester et al, , 1993MacPherson and Davis, 1993). On the basis of these observations, we infer that Vigarano breccia contains the reduced and Allende-like lithologies.…”
Section: Mokoia and Vigarano Breccias: Are All Cv3mentioning
confidence: 72%
“…Kimura and Ikeda (1996) found that many chondrules in Vigarano show alteration features similar to those in Allende: nepheline, sodalite, hedenbergite, fayalitic olivine rims around forsterite grains and fayalitic olivines replacing low-Ca pyroxene phenocrysts. Some CAIs in Vigarano experienced iron-alkali metasomatic alteration of melilite (Sylvester et al, 1992(Sylvester et al, , 1993MacPherson and Davis, 1993). On the basis of these observations, we infer that Vigarano breccia contains the reduced and Allende-like lithologies.…”
Section: Mokoia and Vigarano Breccias: Are All Cv3mentioning
confidence: 72%
“…All of these are listed in Table 1 except for 1623-8, for which the INAA data of Sylvester et al (1992) were used. In the case of the INAA data for E60, the quoted errors on Table 1 are the 1σ uncertainties due only to counting statistics.…”
Section: Major Element Bulk Compositionsmentioning
confidence: 99%
“…A fourcomponent system can be plotted on a ternary diagram by projecting the compositions from the fourth component, which is typically the liquidus phase (e.g., Stolper, 1982). We have plotted compositions ofAXCH-1471 and AXCHI371 and AI-rich chondrules from Sheng et al (1991) on the diagram diopside-tridymite-spinel projected from anorthite (Fig.…”
Section: Constraints On Nebular Timescalesmentioning
confidence: 99%